Pengaruh Literasi Keuangan Syariah dan Kepercayaan Terhadap Minat Masyarakat Bandar Parkland, Klang Selangor, Malaysia, Melakukan Transaksi di Bank Islam - Ade Julia Sari; Riyan Pradesyah (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
This study aims to determine the effect of Islamic financial literacy and trust on the interest of the people of Bandar Parkland, Klang Selangor, Malaysia in conducting transactions at Islamic banks. This study used primary data using a questionnaire method of 120 respondents using nonprobability sampling technique. This study uses a multiple linear regression analysis model to determine the factors that influence the interest of the people of Bandar Parkland, Klang Selangor in conducting transactions at Islamic banks. The results showed that the Islamic financial literacy variable partially had a positive and significant effect on interest in public transactions, the trust variable partially had a positive and significant effect on interest in public transactions. Simultaneously Islamic financial literacy and trust have a positive and significant effect on interest in public transactions with a coefficient of determination of R-Square of 74.4%..